2000
DOI: 10.1073/pnas.190312697
|View full text |Cite
|
Sign up to set email alerts
|

Position-specific trapping of topoisomerase I–DNA cleavage complexes by intercalated benzo[ a ]- pyrene diol epoxide adducts at the 6-amino group of adenine

Abstract: DNA topoisomerase I (top1) is the target of potent anticancer agents, including camptothecins and DNA intercalators, which reversibly stabilize (trap) top1 catalytic intermediates (cleavage complexes). The aim of the present study was to define the structural relationship between the site(s) of covalently bound intercalating agents, whose solution conformations in DNA are known, and the site(s) of top1 cleavage. Two diastereomeric pairs of oligonucleotide 22-mers, derived from a sequence used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…A previous study by Pommier et al (37) addressed the effects of BPdA adducts on the nonscissile strand opposite a preferred T2 cleavage site for human topoisomerase I (equivalent to the ϩ1A position in our numbering system). They found that the R diastereomer increased the extent of cleavage at the T2 site, whereas the S diastereomer completely suppressed cleavage at the T2 site and instead triggered cleavage at a new site 2 nucleotides upstream.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Pommier et al (37) addressed the effects of BPdA adducts on the nonscissile strand opposite a preferred T2 cleavage site for human topoisomerase I (equivalent to the ϩ1A position in our numbering system). They found that the R diastereomer increased the extent of cleavage at the T2 site, whereas the S diastereomer completely suppressed cleavage at the T2 site and instead triggered cleavage at a new site 2 nucleotides upstream.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that cleavage of Top1 to the 80-kDa form does not prevent its nuclear localization (38) and that 80-kDa Top1 retains its ability to form Top1cc in cells exposed to camptothecin (7). In vitro experiments have further demonstrated that truncated 68-kDa C-terminal recombinant Top1 is still catalytically active (37).…”
Section: Caspase-3-cleaved Top1 Is Preferentially Involved In the Apomentioning
confidence: 99%
“…Although the N-terminal domain of Top1 is dispensable for Top1 catalytic activity (37), it binds to the E3 ubiquitin ligase Topors (47). Top1 ubiquitination and subsequent degradation by the 26 S proteasome (48) have been suggested as an early step in the repair of Top1cc prior to tyrosyl-DNA phosphodiesterase (Tdp1) action (49).…”
Section: Caspase-3-cleaved Top1 Is Preferentially Involved In the Apomentioning
confidence: 99%
“…Differences in the distribution of mutations induced by specific BcPh dA adducts have been observed (64), suggesting that the stereochemistry of these BcPh DEs may influence DNA-metabolic events such as the fidelity of translesion DNA synthesis (62). Although DNA polymerases are obvious targets, the ability of PAH-DE adducts in DNA to interact adversely with other enzymes such as topoisomerases (25,26) may also contribute to their carcinogenic effects. Our present findings that helicases are inhibited by these adducts in a strand-specific and stereospecific manner suggest a further mechanism whereby these lesions could contribute to genetic damage and cell transformation.…”
Section: Effect Of a Bcph Adduct On Blm And Uvrd Helicase Activity-thmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbon (PAH) 3,4-diol 1,2-epoxide (DE)-DNA adducts have been used by us as tools to probe the interactions between other DNA-processing enzymes such as topoisomerases (25,26) and their DNA substrates as well as to elucidate possible molecular mechanisms for the induction of cancer by these DNA lesions. In this study, we examined the effects of site-specific benzo[c]phenanthrene (BcPh) DE adducts at N 6 of deoxyadenosine (Scheme I) positioned centrally in the double-stranded region of a forked DNA duplex substrate on the unwinding activity catalyzed by WRN helicase.…”
mentioning
confidence: 99%